2016
DOI: 10.1016/j.ajem.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Association of triage time Shock Index, Modified Shock Index, and Age Shock Index with mortality in Emergency Severity Index level 2 patients

Abstract: In nontrauma adult patients, triage time SI, MSI, and Age SI are superior to blood pressure for mortality prediction in ESI level 2. They can be used alone or in combination with similar results, but their low sensitivity and specificity make them usable only as an adjunct for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 29 publications
(33 reference statements)
1
23
0
2
Order By: Relevance
“…Similar data were also obtained by other researchers. In particular, one study showed that the low sensitivity and specificity of the stress index as a prognostic index of mortality allows using it as an auxiliary means only; the same applies to high‐frequency heart rate variability parameters—they can potentially be used as an auxiliary diagnostic method in combination with other methods …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar data were also obtained by other researchers. In particular, one study showed that the low sensitivity and specificity of the stress index as a prognostic index of mortality allows using it as an auxiliary means only; the same applies to high‐frequency heart rate variability parameters—they can potentially be used as an auxiliary diagnostic method in combination with other methods …”
Section: Discussionmentioning
confidence: 99%
“…Similar data were also obtained by other researchers. In particular, one study showed that the low sensitivity and specificity of the stress index as a prognostic index of mortality allows using it as an auxiliary means only 55 ; the same applies to high-frequency heart rate variability parameters-they can potentially be used as an auxiliary diagnostic method in combination with other methods. 46 In regards to the data provided in literature and data obtained during this study, it was inexpedient to determine the class of the functional dependency between age and heart rate variability indices or the specific type and parameters of the said dependency.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who died on hospital arrival or at the accident scene were not included in the study. Detailed patient information retrieved from the Trauma Registry System of our institution included the following: age; sex; SBP and HR assessed by the nursing staff upon arrival at the triage desk of the ED; SI, defined as the ratio of HR/SBP; MSI, defined as HR divided by MAP = (2 × DBP + SBP) ÷ 3 [ 18 , 23 ]; and Age SI, defined as age multiplied by SI, which accounts for the age of the patient in addition to the factors addressed by SI [ 20 , 23 ]. The pre-existing comorbidities and chronic diseases noted included diabetes mellitus (DM), hypertension (HTN), coronary artery disease (CAD), congestive heart failure (CHF), cerebrovascular accident (CVA), end-stage renal disease (ESRD) and abnormal bodyweight as defined by the World Health Organization [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Comparison with Previous Models. We compared the XGBoost model with severity scores Shock Index (SI), Modified Shock Index (MSI), and Aged Shock Index (ASI) 9,11 where SI = HR/SBP; MSI = HR/(2/3 × DBP + 1/3 × SBP); ASI = Age × SI.…”
Section: Machine Learning Modelmentioning
confidence: 99%
“…The ESI relies heavily on provider judgment which can lead to inaccuracy and misclassification. 9,10 Differentiating between levels 2 and 3 is a challenging task, 11 and ESI level 3 is assigned to a largely diverse ill patient group. 12 Artificial intelligence (AI) algorithms offer advantages for creating predictive clinical applications because of flexibility in handling large datasets from electronic medical records (EMR).…”
Section: Introductionmentioning
confidence: 99%